Moffie [videorecording (DVD)] - Hermanus, Oliver; Hermanus, Oliver; Brümmer, Kai Luke; Immelman, Barbara-Marie; Kirch, Michael; Van der Merwe, André Carl (Shout! Factory, 2022)
Set in the early 1980s, follows the story of a South African teenager who must complete two years of compulsory military service in the South African Defence Force to defend the apartheid regime while trying to hide his homosexuality.